A New Two-Wing Chaotic System with Line Equilibrium, its Analysis, Adaptive Synchronization and Circuit Simulation - Vaidyanathan, Sundarapandian; Sambas, Aceng; Fransisca, Diandra Chika; Mohamed, Mohamad Afendee; Mamat, Mustafa (International Journal of Engineering and Technology, 2018)
This work reports a new three-dimensional chaotic system with line equilibrium and two equilibrium points on the (x, y) plane. A qualitative analysis has been conducted on the system with the aid of bifurcation diagram, Lyapunov exponents spectrum, etc. It is shown that the new chaotic system is dissipative. Since the new chaotic system has infinitely many equilibrium points, it exhibits hidden attractor. Using adaptive control, global chaos synchronization of the new chaotic system with itself is established using Lyapunov stability theory. Finally, a circuit simulation of the new chaotic system with line equilibrium is carried out via MultiSim and the feasibility of implementing the new chaotic system is established.
Keywords: Chaos; chaotic systems; line equilibrium; synchronization; circuit simulation